PENGARUH FINANCIAL DISTRESS, KEPEMILIKAN PUBLIK, AUDIT DELAY, DAN KEPEMILIKAN TERKONSENTRASI TERHADAP AUDITOR SWITCHING : THE EFFECT OF FINANCIAL DISTRESS, PUBLIC OWNERSHIP, AUDIT DELAY, AND CONCENTRATED OWNERSHIP ON SWITCHING AUDITORS - Irjanti, Fany Audia; Nur DP, Emrinaldi; Rasuli, M (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The objective of this research is to examine the impact of financial distress, public ownership, audit delay, and concentrated ownership on auditor switching within the context of property and real estate firms listed on the IDX between 2017 and 2021, comprising a total of 49 companies. The research employed a purposive sampling approach to select 21 companies that fulfilled the research criteria. The study relied on secondary data extracted from the financial reports of these companies and involved a multiple linear regression analysis. The results indicate that financial distress exerts a negative influence on auditor switching, whereas public ownership and audit delay exhibit a positive association with auditor switching. In contrast, concentrated ownership does not demonstrate a significant effect on auditor switching. These findings provide valuable insights for both firms and investors, enabling them to make well-informed decisions concerning auditor switching and its associated determinants, including financial distress, public ownership, and audit delay